2006
DOI: 10.1038/sj.bdj.4813309
|View full text |Cite
|
Sign up to set email alerts
|

Why do dentists struggle with removable partial denture design? An assessment of financial and educational issues

Abstract: AimPublished studies in the international dental literature illustrate that the quality of prescription and fabrication of cobalt-chromium removable partial dentures (CCRPDs) by general dental practitioners frequently fail to comply with ethical and legal requirements. The reasons cited for this in the past have broadly related to either financial or educational issues. The aim of this investigation is to determine the effect of financial and educational factors on the quality of CCRPD design and fabrication b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
44
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 14 publications
5
44
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14][15] They reported specifically on the quality of written prescriptions in the construction of both fi xed and removable partial prostheses. Lynch and Allen 8 stated that the 'literature has highlighted the poor quality of written prescription for removable partial dentures (RPD) and that the problem still exists'.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] They reported specifically on the quality of written prescriptions in the construction of both fi xed and removable partial prostheses. Lynch and Allen 8 stated that the 'literature has highlighted the poor quality of written prescription for removable partial dentures (RPD) and that the problem still exists'.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the authors published the fi rst study which sought to investigate the role of fi nancial and educational factors on the design process for cobalt-chromium removable partial dentures. 12 We found, by comparing samples of written instructions for cobalt-chromium removable par tial dentures provided under a number of different fee struc tures, that there was little difference between the quality of written instructions. 12 This finding is consistent with a simi lar study of endodontic practice in the UK, which found that increased fees did not equate to increased treatment quality.…”
Section: Introductionmentioning
confidence: 99%
“…12 We found, by comparing samples of written instructions for cobalt-chromium removable par tial dentures provided under a number of different fee struc tures, that there was little difference between the quality of written instructions. 12 This finding is consistent with a simi lar study of endodontic practice in the UK, which found that increased fees did not equate to increased treatment quality. 13 However, when we investigated the significance of the educa tional factors, the picture was far more revealing.…”
Section: Introductionmentioning
confidence: 99%
“…Equally there have been a number of surveys which show that in many cases the technicians are asked to design the RPD by the clinician 3,10 and this appears to have been a long standing problem. 14 Previous studies 15 have been carried out which compared the qualifi ed dental surgeons' ability to design partial dentures and communicate the design to the dental technician.…”
Section: Introductionmentioning
confidence: 99%